The Urban Settlement of Refugees, 1923–1930: An Assessment of the Objectives and Policies of the Refugee Settlement Commission (RSC) - Kapokakis, Alkis; Kyramargiou, Eleni; Lafazani, Olga; Tyrovolas, Thanasis (The Historical Review/La Revue Historique, 2025)
This article examines the housing policy pursued by the Refugee Settlement Commission (RSC) for urban refugees in the framework of the implementation of the rehabilitation project, which was financed by foreign loans that were secured in 1924 and 1928 with the mediation of the League of Nations. By analysing data from the reports of the commission and the minutes of its board of directors, we attempt to shed light on the internal logic underlying its planning and the way in which its efforts determined – in conjunction with other factors – the housing conditions of the refugees in urban areas, especially in the numerous settlements that were built around Athens and Piraeus.